The effects of atorvastatin on intimal hyperplasia after endothelial denudation - Mehmet, Balin; Erdogan, Iikay; Mustafa, Yavuzkir; Ilgin, Karaca; Necati, Dagli; Ali, Rahman (Springer, 2007)
[Abstract Not Available]